PERAN PEMULUNG DALAM PENGELOLAAN SAMPAH DAN TIMBULAN SAMPAH DI TPA TERJUN KECAMATAN MEDAN MARELAN KOTA MEDAN TAHUN 2015 - elisabet hutagalung; devi nuraini santi; irnawati marsaulina (Lingkungan dan Kesehatan Kerja, 2015)
ABSTRACTScavengers are groups of people who seek and collect solid waste that still has economic value. The scavengers usually take out the waste in the trash while or in landfill. Supervisory of the landfill was originally not allow scavengers to collect waste in the landfill because they can be exposed to sharp objects and disease. Over time, the scavengers eventually left to work at the landfill. Number of scavengers in TPA Terjun today is 500 people. The role of scavengers at the landfill is still unknown whether it can help reduce landfill waste in the landfill.This research is a descriptive research with quantitative analysis. The goal is to find out what the role of a scavenger in the management of waste in the landfill. The sample size observed was 30 people.The research result shows that the volume of waste that goes into TPA Terjun every day was 3.868,57 m3 while the amount of waste that can be managed by scavengers every day is 89,02 m3. Thus, the volume of landfill waste left in TPA Terjun every day was 3.779,55 m3.The conclusion from this study is that the scavenger role in waste management and solid waste generation did not show a reduction in the volume of landfill waste in TPA Terjun. Ability scavengers in reducing the volume of waste in TPA Terjun only by 2,3%. Thus, the percentage of residual landfill waste in TPA Terjun every day is 97,7%.The government should develop a technology that not only destroy the waste but also making use of waste as alternative energy sources as well as supporting the role of scavengers in reducing waste in TPA Terjun, Medan.Keywords : Scavengers, Waste Management, Volume of Waste